Cost of hospitalization for foodborne diarrhea: A case study from Vietnam - Hoang Van Minh; Tran Tuan Anh; Anh Duc Ha; Hung Nguyen-Viet (XMLink, 2015)
Vietnam is undergoing a rapid social and economic developments resulting in speedy urbanization, changes in methods for animal production, food marketing systems, and food consumption habits. These changes will have major impacts on human exposures to food poisoning. The present case study aimed to estimate hospitalization costs of foodborne diarrhea cases in selected health facilities in Vietnam. This is a facility-based cost-of-illness study conducted in seven health facilities in Northern Vietnam. All suspect cases of foodborne diarrhea, as diagnosed by doctors, who admitted to the studied health facilities during June-August, 2013 were selected. Costs associated with hospitalization for foodborne diseases were estimated from societal perspective using retrospective approach. We included direct and indirect costs of hospitalization of foodborne diarrhea cases. During the study period, 87 foodborne diarrhea cases were included. On average, the costs per treatment episode and per hospitalization day for foodborne diarrhea case were US$ 106.9 and US$ 33.6 respectively. Indirect cost (costs of times to patient, their relatives due to the patient's illness) made up the largest share (51.3%). Direct medical costs accounted for 33.8%; direct non-medical costs (patient and their relatives) represented 14.9%. Cost levels and compositions varied by level of health facilities. More attentions should be paid on prevention, control of foodborne diarrhea cases in Vietnam. Ensuring safety of food depends on efforts of everyone involved in food chain continuum, from production, processing, and transport to consumption.